Halal exporting: Empowering Malaysian SMEs in the global market - Ahamat, Amiruddin; Che Pee @ Che Hanapi, Ahmad Naim; Jaafar, Adib Akram (Penerbit UTeM Press, 2025)
"Halal Exporting: Empowering Malaysian SMEs in the Global Market" is a comprehensive reference for small and medium-sized firms (SMEs) in Malaysia navigating the ever-changing and developing global halal market. This book examines the significance and global potential of halal goods and services, giving a strong foundation for understanding why halal exporting is more than a passing trend but a significant opportunity for business growth. With a focus on the Malaysian context, the voyage begins with an overview of halal products and services, highlighting their global market potential and the difficult process of halal certification. This book presents an overview of Malaysia's thriving halal ecosystem with a focus on the country's role as a global halal hub, supported by robust government initiatives and a well-organised regulatory framework. The book teaches small and medium-sized businesses (SMEs) how to do market research to locate export opportunities by breaking down target markets, examining demand trends, and identifying promising export potential. This practical reference addresses halal logistics, shipping, packaging, and labelling standards, highlighting the importance of halal integrity across the supply chain. This book offers a framework for halal product marketers to use to differentiate themselves in a crowded global industry.